2016
DOI: 10.2174/187443460160101078
|View full text |Cite
|
Sign up to set email alerts
|

Mini Review of Integrated Care and Implications for Advanced Practice Nurse Role

Abstract: Literature related to primary care and behavioral health integration initiatives is becoming abundant. The United States’ 2010 Patient Protection and Affordable Care Act included provisions encouraging increased collaboration of care for individuals with behavioral and physical health service needs in the public sector. There is relatively little known of Advanced Practice Registered Nurses’ (APRNs) roles with integrating primary and behavioral healthcare. The goal of this review article is to: (a) define inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…With regard to the individual predictor results, the Swiss CMHNS and their practice should be developed to ensure better coverage for under-treated groups, like males, with a focus on how CMHNS could be offered to persons with mental health needs outside of the psychiatric system. To put this recommendation into practice, nursing services should be better represented and implemented in primary care, similar to the relevant discourse and development in other countries (DiCenso et al 2007;McIntosh et al 2016).…”
Section: Conclusion Implications For Practicementioning
confidence: 99%
“…With regard to the individual predictor results, the Swiss CMHNS and their practice should be developed to ensure better coverage for under-treated groups, like males, with a focus on how CMHNS could be offered to persons with mental health needs outside of the psychiatric system. To put this recommendation into practice, nursing services should be better represented and implemented in primary care, similar to the relevant discourse and development in other countries (DiCenso et al 2007;McIntosh et al 2016).…”
Section: Conclusion Implications For Practicementioning
confidence: 99%
“…When obstacles to trust, such as competition or role ambiguity, exist, they are likely to stand in the way of optimizing collaboration. A recent review of the role of American advanced nurse-practitioners (ANPs) in relation to others within the MDT concluded that better outcomes are achieved when ANPs have a defined role inclusive of “competencies, leadership, engagement, collaboration, and advocacy” 36. Under the current model of service provision in the Netherlands, similar arrangements for HMs may assist in reducing barriers in MDT collaboration.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known of Advanced Practice Registered Nurses' (APRNs) integrating primary and behavioural healthcare. An American study found implications for the Integrated Care advanced practice nurse to have roles inclusive of competencies, leadership, engagement, collaboration and advocacy [6]. Halliday et al [7] in exploring perceptions of the role of the advanced nurse practitioner in a 'hospital at day' setting found similar competencies expressed by ward staff.…”
Section: Integration Initiative By Advanced Nurse Practitionersmentioning
confidence: 99%